Advances in ERECTA Family Regulation of Female Gametophyte Development in Arabidopsis thaliana - Han Su; Xiaohu Jiang; Yanfen Liu; Zhuangyuan Cao; Ziqi Liu; Yuan Qin; Qing He; Hanyang Cai (Plants, 2025)
The female gametophyte is central to the reproductive success of flowering plants, with its development being tightly controlled by an intricate network of genes and signaling pathways. A deeper understanding of these regulatory mechanisms is essential for uncovering the complexities of plant growth and development. Recent studies have shed light on various aspects of female gametophyte development, highlighting the role of specific gene and signaling networks. Among these, the ERECTA family of leucine-rich repeat receptor-like kinase (RLK) in Arabidopsis thaliana has emerged as a key player, influencing multiple biological processes, particularly those governing reproductive development of the female gametophyte. This review focuses on the significant progress made in understanding the ERECTA family’s involvement in germline cell development, emphasizing its functional roles and signaling mechanisms in female gametophyte development.